On the köthe-toeplitz duals of some generalized sets of difference sequences - Asma, Ç.; Çolak, R. (Walter de Gruyter GmbH, 2000)
In this paper we define the sequence sets l?(?, ?, p), c(?,?,p) and C0(?, ?, p), and give ?- and ?- duals of these sets and the sequence space l?(?rp) defined by Mursaleen et al. These sets generalizes some sets defined by Ahmad and Mursaleen [1], and Malkowsky [6]. © 2000 Warsaw University.
Keywords: Difference sequences; ?- and ?duals